Solventless Microextration Techniques for Pharmaceutical Analysis: The Greener Solution - Mohamed, Heba M. (Frontiers in Chemistry, 2022)
Extensive efforts have been made in the last decades to simplify the holistic sample preparation process. The idea of maximizing the extraction efficiency along with the reduction of extraction time, minimization/elimination of hazardous solvents, and miniaturization of the extraction device, eliminating sample pre- and posttreatment steps and reducing the sample volume requirement is always the goal for an analyst as it ensures the method’s congruency with the green analytical chemistry (GAC) principles and steps toward sustainability. In this context, the microextraction techniques such as solid-phase microextraction (SPME), stir bar sorptive extraction (SBSE), microextraction by packed sorbent (MEPS), fabric phase sorptive extraction (FPSE), in-tube extraction dynamic headspace (ITEX-DHS), and PAL SPME Arrow are being very active areas of research. To help transition into wider applications, the new solventless microextraction techniques have to be commercialized, automated, and validated, and their operating principles to be anchored to theory. In this work, the benefits and drawbacks of the advanced microextraction techniques will be discussed and compared, together with their applicability to the analysis of pharmaceuticals in different matrices.